Rehabilitation Management of Intensive Care Unit-acquired Weakness (ICU-AW): A Narrative Review - Nazir, Arnengsih; Anggraini, Gabriela (Surabaya Physical Medicine and Rehabilitation Journal, 2024)
Background: Intensive Care Unit-acquired weakness (ICU-AW) is one of the most common neuromuscular disorders affecting intensive care unit (ICU) patients' outcomes and clinical course. ICU-AW is found in 30-50% of patients and increases to 67% in sepsis-critically ill patients. Prolonged ICU stay, the difficulty of weaning from the ventilator, higher hospitalization costs, and an increase in mortality, as well as long-term morbidity, are associated with ICU-AW. ICU-AW causes skeletal muscle weakness, including respiratory muscles, which results in complications that continue even years after being discharged from the hospital. Aim: To describe the rehabilitation management of ICU-AW and provide the information needed clinically to manage these patients. Methods: The authors reviewed all types of articles without time filtering using PubMed and Google Scholar databases with "ICU-AW”, "ICU-related weakness”, "rehabilitation”, and "early mobilization” used as keywords. Results: Rehabilitation management can be done as early as possible, beginning while the patient is still in the ICU. Early mobilization programs require teamwork consisting of doctors, therapists, and nurses. Physical activity and early mobilization in the ICU must be carried out with consideration for safety. Monitoring patient safety before and during mobilization is an essential factor to be considered. Any mobilization program should be the decision of the ICU care team. Implementation of rehabilitation programs and early mobilization improves outcomes for patients with ICU-AW and should be continued until the follow-up period. Conclusion: The rehabilitation management aiming at preventing and treating ICU-AW should be done since the patient was still in the ICU and under careful consideration of safety aspects.